Agricultural socialized services empowering smallholder rice producers to achieve high technical efficiency: empirical evidence from southern China - Cai, Baozhong; Shi, Fang; Meseretchanie, Abate; Betelhemabraham, Geremew; Zeng, Rong (Frontiers in Sustainable Food Systems, 2024)
Introduction This study emphasizes the importance of agricultural efficiency for food security and income generation, especially among smallholder rice farmers in southern China. Limited access to essential agricultural services hinders productivity in this region. The study highlights the significant potential of agricultural socialized services (ASS) in improving the technical efficiency of smallholder rice production. Methods To analyze the impact of ASS on technical efficiency in rice production, we focused on tillage, transplanting, crop protection, and harvest operations. We employed stochastic frontier analysis and collected data from smallholder farmers in Hunan, Jiangxi, and Zhejiang provinces. By estimating the technical efficiency of rice production, we aimed to assess the relationship between ASS and smallholder farmers’ technical efficiency. Results and discussion The results of our analysis revealed that ASS significantly enhance the technical efficiency of rice production among smallholder farmers by supporting agricultural practices such as transplanting, crop protection, and harvest operations. However, we found that the impact of ASS on tillage operations was not statistically significant. Participation in ASS enhances smallholders’ access to modern production techniques, resources, and knowledge, leading to improved technical efficiency. These services also empower smallholder rice producers to adopt sustainable farming practices, access credit, financing, and market information, and promote collective action and cooperation, ultimately influencing technical efficiency. Conclusion This study emphasizes the potential of ASS in improving the technical efficiency of smallholder rice production in southern China. Policymakers and agricultural organizations can use these insights to design interventions that promote efficient practices, enhance productivity, support livelihoods, and ensure food security in the region.